The incremental clinical value of spect-CT in neck region in the treatment of differentiated thyroid cancer with low dose radioiodine-131 for the first therapy - Kamarudin, Abdul Hakim (2020)
Backgrounds Iodine-131 (I-131) whole-body planar scan (WBS) is considered as a routine practice for initial staging, restaging and long term follow up following radioiodine ablation therapy for management of patients with DTC. However, the planar WBS images produce lack of anatomical landmark that will be challenging for image interpretation. SPECT-CT allows to correlate lesions pictured by functional planar imaging with anatomical structures. The adding of anatomical info increases both the sensitivity and the specificity of the scintigraphy results. The specific and precise location and properties of radioiodine uptake in pathological or physiological situations demonstrated that the restriction or pitfall of planar imaging has been removed using SPECT-CT. The purpose of this study is to evaluate the incremental value of SPECT-CT in the management of DTC patients who received low dose I-131 in Hospital USM over planar WBS imaging. Methods Patients who undergo total/near-total thyroidectomy with histopathology confirmed DTC and planned for low dose radioiodine ablation I-131 for first time were recruited into this study. The inclusion criteria were the post-therapy scintigraphy WBS demonstrated sensitive radioiodine uptake in the neck and no other distant irregular foci elsewhere. The selected patient undergone SPECT-CT procedure during same setting. The image for planar WBS imaging and SPECT-CT of the neck was compared by the doctor and the number of foci, type of thyroid carcinoma, TNM staging were recorded. Results Patients recruited in the study are 80% papillary, 10% follicular and 10% Hurtle thyroid carcinoma. The average diagnostic benefit of SPECT-CT in the neck for the lesion is 76%. As a result, SPECT-CT resulted in the revision of 3 out of 10 patients (30 %), which only contributed by the 45 years or older (n=5), each of which was stage IV. This results in 3 out of 10 patients (30